2016
DOI: 10.1007/s00209-016-1823-6
|View full text |Cite
|
Sign up to set email alerts
|

Injective labeled oriented trees are aspherical

Abstract: A labeled oriented tree is called injective, if each vertex occurs at most once as an edge label. We show that injective labeled oriented trees are aspherical. The proof uses a new relative asphericity test based on a lemma of Stallings.MSC: 57M20, 57M05, 20F05

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…There is a large corpus of results which are related to ours and is mostly contained in [4], [5], [8], [10], [14], [18], [19], [20], [22], [23], [24], [25], [26], [30], [32], [16] and [43].…”
Section: Introductionmentioning
confidence: 99%
“…There is a large corpus of results which are related to ours and is mostly contained in [4], [5], [8], [10], [14], [18], [19], [20], [22], [23], [24], [25], [26], [30], [32], [16] and [43].…”
Section: Introductionmentioning
confidence: 99%
“…See Bogley [1] and Rosebrock [9] for surveys on the Whitehead Conjecture. Recently the authors have shown that injective labeled oriented trees are aspherical [4]. Here we show that certain injective word labeled oriented graphs are aspherical (in fact, diagrammatically reducible, a strong combinatorial version of asphericity).…”
Section: Introductionmentioning
confidence: 52%
“…Relative vertex asphericity for pairs of 2-complexes K ⊆ L already appeared in a previous article [9] by the authors, where it was used to establish asphericity of injective LOT-complexes. Other and related notions of relative combinatorial asphericity are in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In [12] Huck and Rosebrock proved that prime injective labeled oriented trees satisfy Sieradski's coloring test. In [9] the authors showed that injective labeled oriented trees are aspherical. We strengthen this result here by showing that injective labeled oriented trees satisfy a relative weight test with weights 0 and 1 and hence are VA.…”
Section: Introductionmentioning
confidence: 99%